Pemanfaatan Greenhouse Secara Optimal dalam Peningkatan Kualitas Lingkungan Asri di SMP Negeri 1 Pamboang - Wahyudi, Agung; Nurfadilah, Nurfadilah; Lewa, Hatifa Hauleni; M, Nurinsania; Arsyad, Arie Arma (JKM: Jurnal Kemitraan Masyarakat, 2025)
One of the school environments that can be used as a learning resource is a greenhouse. A greenhouse is a building where various types of plants are cultivated. Greenhouses or green houses generally have walls and roofs made of plastic or glass that allow light to enter the house so that the light can make plants grow optimally. The problem at SMP Negeri 1 Pamboang is that there is a Greenhouse building but it is rarely noticed. Referring to the above problems, we took a solution, namely by revamping the Greenhouse. The method we use is the practical method, namely the method by directly intervening in the location of the Greenhouse improvement. The result is that the greenhouse looks better than the previous condition and the school community's awareness increases on the importance of protecting the environment.